A universal parameter to predict subaerial landslide tsunamis? - Heller, Valentin; Hager, Willi H. (MDPI, 2014)
The significance of the impulse product parameter P is reviewed, which is believed to be the most universal parameter for subaerial landslide tsunami (impulse wave) prediction. This semi-empirical parameter is based on the streamwise slide momentum flux component and it was refined with a multiple regression laboratory data analysis. Empirical equations based on P allow for a simple prediction of wave features under diverse conditions (landslides and ice masses, granular and block slides, etc.). Analytical evidence reveals that a mass sliding down a hill slope of angle 51.6° results in the highest waves. The wave height ―observed‖ in the 1958 Lituya Bay case was well predicted using P. Other real-world case studies illustrate how efficient empirical equations based on P deliver wave estimates which support hazard assessment. Future applications are hoped to further confirm the applicability of P to cases with more complex water body geometries and bathymetries. Keywords: hazard